Portofolio Optimal dan Pengelompokan Perusahaan Berdasarkan Pengaruh Komoditas Dunia - Berry Yuliandra; Alizar Hasan; Rahmad Rezeki (Jurnal Optimasi Sistem Industri, 2017)
The awarding of investment grade to Indonesian Stock Exchange marked an excellent development in the national capital market. This could be the key to attracting foreign investors that will further integrate the Indonesia capital market with international markets. Increasingly integrated capital market will also be more vulnerable to international issues such as the volatility of global stock indices as well as the volatility of world commodity prices (crude oil, CPO, gold etc.) as indicated by IHSG response to these issues. To minimize risk and maximize the return are the main goal of investment. Both of these two objectives can be achieved through stocks diversification and the portfolio development. Optimal portfolio requires the right stocks diversification. Therefore, investor needs to have information about which stocks are affected and unaffected by world commodity prices prior to diversifying. The goal of this research is to examine the way to form optimal portfolio from the group of companies listed in Indonesian Stock Exchange and affected by world commodity prices. Augmented Dickey Fuller (ADF) method used for stationary test of time series data and residual regression models. Regression Analysis conducted for co-integration test between commodity prices and IHSG. Error Correction Model used for correcting short-term errors. Optimal portfolio formed with Single Index Model and Treynor Index used to measure the optimal portfolio performance. Result of the study showed that gold, crude oil, platinum, rubber, corn, cotton, and Arabica coffee are the global commodities that can be used to predict the direction of IHSG movement.